Kebutuhan Perawat terhadap Pengembangan Kapasitas Leadership di Tatanan Pelayanan Kesehatan Komunitas - Rina Kusmayanti; Hana Rizmadewi Agustina; Kurniawan Yudianto (Jurnal Keperawatan Silampari, 2023)
This study aims to analyze the needs of nurses for leadership development in community health service settings. The research method used in this literature review is a narrative review. The literature sources used in the article search process are databases from PubMed, EBSCO cinahl, and Google Scholar. The study's results show that nurse leadership capacity development analysis consists of leadership, commitment, resources, culture, spirituality, and technology. Capacity building is a process of developing and improving organizational resources' skills, talents, and capabilities as a necessity to grow the organization in an era of rapid change. Implementing capacity building for nurse leadership in the community has yet to run optimally. This has implications for an organizational structure that only works effectively due to weak coordination between nurses and other health workers. Commitment, communication, collaboration, and delegation of staff responsibilities are soft, and the use of health resources could be more optimal. Capacity building is an effort to improve the ability of nurses in terms of knowledge, skills, attitudes, and behavior. In conclusion, community leadership is different from specific organizations or individuals. Leadership in society must be able to quickly assess needs and trends, use all available data and information sources, then develop innovative actions, and plan and evaluate results using quality monitoring systems. Keywords: Leadership, Community, Capacity Building, Nurse